STUDY OF THE VARIABILITY OF Y CHROMOSOMAL MICROSATELLITE LOCI CHARACTERISTIC TO UZBEK POPULATION - Kurganov; Kurganov, S.K; Axmedova, D.Sh.; Normatov, A.E; Tosheva, D.M. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
Aimed to investigate the haplotypes and allele frequencies for the 17 Y-STR loci in Uzbekistan population. Material and Methods: The subjects of the study were blood samples and dried saliva on sterile gauze tampons, selected from 1900 individuals. Results: This population was demonstrated 1000 haplotypes, of which 899 (Tashkent – 100, Fergana – 73, Andijan – 84, Namangan – 36, Sirdarya – 54, Djizax – 77, Samarqand – 77, Kashqadarya – 71, Surxandarya – 46, Buxara – 97, Navoiy – 48, Xorezm – 90 and from Republic Karakalpakistan – 93) were unique. The gene diversity was 0.996 (standard error: 0.005). The haplotype diversity calculated from the 17 Y-STR loci was 0.899 and the discrimination capacity was 0.9223. The DYS385 locus showed the highest gene diversity value (0.8936), while the DYS437, DYS389I, DYS391, DYS392 loci showed the lowest gene diversity value (0.49-0,55). This database of 17 Y-STR loci for the Uzbekistan population would be useful in forensic examinations and human genetic studies. Conclusions: Studies of the variability of 17 Y-STR loci in the Y-chromosome of the Uzbek population have demonstrated a high level of heterogeneous diversity of the gene pool of the indigenous population of Uzbekistan. Getting the result showed a mixed nature of the population